Impacto de la ampliación hacia el este de la Unión Europea : convergencia y estabilidad - García Menéndez, José Ramón (Estudios Internacionales, 2003)
The enlargement of the European Union is one of the next challenges facing Europe. It is a broad subject and in which there is a diversity of opinions about its effects and implications, the measures that should be carried out, the conditions of the negotiations, the policies and reforms to be applied, etc. This article summarizes the evolution of the enlargement process, from the situation of the candidate countries to the latest negotiations for the next accession. Some of the effects of enlargement are analyzed, placing special emphasis on those issues of greatest controversy, and then examining the progress of the negotiations with the candidate countries, some issues that could influence the convergence and stability of the process, and the implications of enlargement for third countries.